(untitled) (Nativa, 2016)
O objetivo deste trabalho foi testar 10 modelos hipsométricos para eucalipto em sistema de integração lavoura-pecuária-floresta. O experimento foi implantado no município de Cáceres –MT em novembro de 2010. O plantio do eucalipto foi realizado em fileiras triplas (renques), com espaçamento de 3x3 m nos renques e 23 m entre os renques. Os valores do coeficiente de correlação múltipla (ryŷ) variaram entre 0,6773 e 0,8239, sendo o maior valor pertencente à equação gerada pelo modelo 5. O modelo 5 também apresentou a menor raiz quadrada do erro médio em percentagem (RQEM%) de 7,78, sendo o mais acurado para estimativa da altura de eucalipto em sistema de integração lavoura-pecuária-floresta. Palavras-chave: sistema agroflorestal, altura total, modelos de regressão. HYPSOMETRIC MODELS FOR EUCALYPTUS IN A SYSTEM FOR INTEGRATING CROP-LIVESTOCK-FOREST ABSTRACT The objective of this study was to test 10 hypsometric models for eucalyptus in a system for integrating crop-livestock-forest. The experiment was implemented in the city of Cáceres, MT, Brazil, in November 2010. The planting of eucalyptus was held in triple lines (rows), with distances of 3x3 m in the rows and 23 m among the rows. The multiple correlation coefficient values (ryŷ) ranged from 0.6773 to 0.8239, where the highest value belongs to the equation generated by the model 5. The model 5 also showed the lowest square root of average error in terms of percentage (RQEM%), totaling 7.78, and it was the most accurate value for estimating the height of eucalyptus in the system for integrating crop-livestock-forest. Keywords: agroforestry system, total height, regression models. DOI: http://dx.doi.org/10.14583/2318-7670.v04n01a03